2014
DOI: 10.1007/s00436-014-4113-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of pathogenic potential of Anisakis physeteris and Anisakis paggiae in Wistar rats

Abstract: Anisakis morphotype I is the principal etiologic agent of human anisakiasis, with differences in pathogenicity found between the Anisakis simplex s.s. and A. pegreffii species; however, the role of morphotype II larvae in this illness is not well understood. The purpose of this study is to verify the ability of morphotype II larvae to invade tissues via the experimental infection of Wistar rats, an animal model which simulates infection in humans. In the in vivo assay, 7.1% (4/56 L3 morphotype II) showed patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[136][137][138][139][140][141][142] There has been speculation that some species of Anisakis may be more infective than others; however, A. simplex, A. pegreffii, A. paggiae and A. physeteris are all able to infect rats. 143,144 In both rats and mice, Anisakis infection leads to similar pathology to humans, with infiltration of eosinophils and neutrophils and formation of granulomas with multinucleate giant cells. In primary infection in rats, oedema was mild, with fibrous and granulomatous changes appearing around day 7, foreign giant cells by week 5 and a granuloma by week 11.…”
Section: Animal Studies Of Anisakis Immunologymentioning
confidence: 97%
See 1 more Smart Citation
“…[136][137][138][139][140][141][142] There has been speculation that some species of Anisakis may be more infective than others; however, A. simplex, A. pegreffii, A. paggiae and A. physeteris are all able to infect rats. 143,144 In both rats and mice, Anisakis infection leads to similar pathology to humans, with infiltration of eosinophils and neutrophils and formation of granulomas with multinucleate giant cells. In primary infection in rats, oedema was mild, with fibrous and granulomatous changes appearing around day 7, foreign giant cells by week 5 and a granuloma by week 11.…”
Section: Animal Studies Of Anisakis Immunologymentioning
confidence: 97%
“…Animal models have been used to try to dissect immunological mechanisms of disease, clarify aspects of responses to live and dead larvae and determine the pathogenicity of various Anisakis species . There has been speculation that some species of Anisakis may be more infective than others; however, A. simplex , A. pegreffii , A. paggiae and A. physeteris are all able to infect rats …”
Section: Introductionmentioning
confidence: 99%
“…This has been often related to peculiar abilities that lead to pathogenicity, but other factors should be considered, such as their occurrence in fishes that are commonly eaten raw, or distribution in countries where the molecular diagnosis of human cases is well established in research and diagnostic laboratories. Only two studies investigated the pathogenic potential of species other than A. simplex and A. pegreffii , revealing that Anisakis physeteris and Anisakis paggiae could be capable, to a lesser extent, of attaching to and penetrating the gastrointestinal wall of model animals [ 36 ] and the ability of Contracaecum osculatum to elicit a granulomatous reaction at the penetration site in pig gastrointestinal mucosa [ 37 ].…”
Section: Advances In the Genomics Of Anisakid Speciesmentioning
confidence: 99%
“…Numerous investigations of clinical cases have documented the pathogenicity of the anisakid worm larvae in man which has called for further investigations using experimental animals in order to further characterize pathogenesis. Rats, rabbits, dogs and pigs may be applied for experimental infections and studies have shown that several species of Anisakis, Pseudoterranova decipiens, Contracaecum osculatum and Contracaecum multipapillatum penetrate the mucosa of the gastro-intestinal tract (Desowitz, 1986;Vidal-Martínez et al, 1994;Barros et al, 2004;Romero et al, 2014;Strom et al, 2015;Buchmann & Mehrdana, 2016).…”
Section: Introductionmentioning
confidence: 99%